From Conflict to Classroom: Understanding School-Community-Family Partnerships in Conflict-affect Myanmar (Journal of Education and Development, 2024)
This study explores how schools, communities, and families in Pekon Township, Myanmar, collaborate to sustain education amidst conflict. Being confronted with challenges including violence and displacement, Pekon township has witnessed the establishment of over 80 community schools, providing education to over 12,000 students. The study explores through interviews and group discussions uncovering strategies such as flexible learning schedules, emotional well-being support, and community-led initiatives to ensure students' educational and emotional well-being. The findings highlight the importance of resilience, adaptive learning, and local leadership in overcoming educational barriers. This research contributes valuable insights into sustaining education in conflict-affected areas, emphasizing the critical role of community involvement and innovative practices in navigating adversity.